Species III - Dwiggins, David; Mancuso, Frank Jr.; Ripley, Ben; Feldman, Dennis; Turner, Brad; Dunne, Robin; Knepper, Rober,t; Cooke, Amelia; Pitoc, J.P.; Warren, Michael; Neame, Christopher; Henstridge, Natasha; et al. (Santa Monica, California Metro-Goldwyn-Mayer home entertainment, 2005)
The mating game gets deadly. In the ongoing fight for supremacy between mankind and the human-alien hybrids, a fatal hybrid weakness has given humans the advantage. Until now. When Eve gives birth to Sara, she develops into the most perfect alien form.
Starring Robin Dunne, Robert Knepper, Amelia Cooke, J.P. Pitoc, Michael Warren, Christopher Neame, Natasha Henstridge, Sunny Mabrey
Dolby Digital.
Printed and exclusively distributed by Viva Video, Inc.
Keywords: Human-alien encounters -- Drama